Interruptions can Change the Perceived Relationship between Accuracy and Confidence. (September 2015) - Zish, Kevin; Hassanzadeh, Shiva; McCurry, J. Malcolm; Trafton, J. Gregory
Interruptions are disruptive in that they can decrease accuracy and the time taken to complete a task. In fields such as aviation and medicine, interruptions can not only reduce performance but lead to egregious outcomes. In such situations, confidence in whether a procedure has been completed may become a crucial aspect of judging where to resume a task. This paper demonstrates that interruptions both decrease accuracy and reduce confidence. More importantly, interruptions change the relationship between accuracy and confidence, reducing the likelihood that participants can determine where to resume appropriately.